Revitalisasi Perpustakaan SMK Bina Pangudi Luhur Berbasis Teknologi Informasi dan Komunikasi - Kangko, Danang Dwijo; Pranajaya, Pranajaya; Wardiyono, Wardiyono (Universitas Nusantara PGRI Kediri, 2021)
The use of information and communication technology (ICT) in libraries is mandated by Law No. 43 of 2007 on Libraries. Unfortunately, many school libraries find it difficult to carry out this mandate. The SMK Bina Pangudi Luhur Library is one of them. Revitalizing the SMK Bina Pangudi Luhur Library aims to provide information access and library services based on information and communication technology (ICT). This community service activity method is carried out in three stages, preparation, implementation, and evaluation. The preparation stage was carried out by analyzing the needs of the SMK Bina Pangudi Luhur Library. The implementation stage includes installing computer hardware and software, online and offline training, and data entry for the collection of the SMK Bina Pangudi Luhur Library. The evaluation phase includes evaluation and mentoring activities. The result of this community service activity is the availability of an automated library management system based on the School Integrated Library System and Barcode System. This activity has also succeeded in adding to the availability of digital information sources in electronic school books and electronic folklore books that can be accessed through devices at the SMK Bina Pangudi Luhur Library. Teachers and employees also gained new knowledge about library management based on the School Integrated Library System and Barcode System. It can be a provision for running library operations by utilizing information and communication technology (ICT).